Effectiveness of Reproductive Health Education on Knowledge, Attitudes, and Intention to Use Hormonal Contraception among Women of Reproductive Age in Makassar City - Nia Karuniawati; Suhermi Suhermi; Andi Masnilawati (Pancasakti Journal Of Public Health Science And Research, 2026)
This study analyzed the effectiveness of reproductive health education on knowledge, attitudes, and intentions to use hormonal contraception. The research was conducted in the service area of the Kassi-Kassi Community Health Center, Makassar City, from September to December 2025 and involved 54 respondents. A quasi-experimental method with a one-group pretest–posttest design was employed. Participants were selected using a purposive sampling technique based on predefined inclusion criteria. Data were analyzed using SPSS software, and statistical significance was assessed using the chi-square test. The results demonstrated a statistically significant effect of reproductive health education on respondents’ knowledge (p = 0.001), attitudes (p = 0.001), and intentions to use hormonal contraception (p = 0.001) after the intervention. Overall, the findings indicate that reproductive health education is effective in increasing knowledge, fostering positive attitudes, and strengthening the intention to use hormonal contraception among women of childbearing age in the Kassi-Kassi Community Health Center service area, Makassar City.